(untitled) (Journal of Computational Mathematics, 2003)
In this paper, we extend two rectangular elements for Reissner-Mindlin plate [9] to the quadrilateral case. Optimal H^1 and L^2 error bounds independent of the plate thickness are derived under a mild assumption on the mesh partition.